Optical Biopsies and Microscopic Techniques 1996
DOI: 10.1117/12.260803
|View full text |Cite
|
Sign up to set email alerts
|

Optical determination of motility forces in human spermatozoa with laser tweezers

Abstract: Laser tweezers may act as optical force transducers. We report on the determination of intrinsic motility forces of human spermatozoa by employing an 800 nm optical trap. The cellular forces were calculated from calibrated trapping forces. The determination of trapping forces based on a hydrodynamic model for ellipsoidal specimens, the measurement of the minimum laser power required to confine a single cell in the trap, and the calculation of viscous forces during the movement of optically trapped sperm heads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…To convert milliwatts of laser power to trapping force, the basic formula is F = nQP / c , where F is the force, n is the refractive index of the object being trapped divided by the refractive index of the surroundings (Ashkin, 1992; Konig et al ., 1996), P is the power in the trap, and c is the speed of light. Q is a conversion factor that, for objects that absorb some of the trap, has a range of 0–1, where 1 is equivalent to total absorption (Ashkin, 1992; Svoboda and Block, 1994a; Konig et al ., 1996; Neuman and Block, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To convert milliwatts of laser power to trapping force, the basic formula is F = nQP / c , where F is the force, n is the refractive index of the object being trapped divided by the refractive index of the surroundings (Ashkin, 1992; Konig et al ., 1996), P is the power in the trap, and c is the speed of light. Q is a conversion factor that, for objects that absorb some of the trap, has a range of 0–1, where 1 is equivalent to total absorption (Ashkin, 1992; Svoboda and Block, 1994a; Konig et al ., 1996; Neuman and Block, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Q is a conversion factor that, for objects that absorb some of the trap, has a range of 0–1, where 1 is equivalent to total absorption (Ashkin, 1992; Svoboda and Block, 1994a; Konig et al ., 1996; Neuman and Block, 2004). Q is the fraction of momentum transferred to a trapped object, and its value determines whether an object will be trapped (Wright et al ., 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it also requires knowledge of the viscosity of the surrounding medium. As this cannot be easily performed within the cell, the corresponding forces were estimated by assumption of a range of values for chromosomes trapping efficiency that was based on previous chromosome fragment trapping experiments 8 , and experiments to trap sperm heads after removal of their tails 11 19 .…”
mentioning
confidence: 99%
“…In addition to VCL, laser trapping has been used to measure the actual swimming force of human sperm (Tadir et al 1989) as well as sperm from other vertebrate species (Nascimento et al 2006). The ideal optical tweezer wavelengths for sperm trapping fall between 800 and 1064 nm (Konig et al 1996). Using laser tweezers, Patrizio found that the swimming force of sperm dramatically increases upon addition of pentoxifylline (Patrizio et al 2000), while Nascimento studied sperm competition based on mating type (polygamous versus monogamous) in several primate species, including human (Nascimento et al 2008a).…”
Section: Introductionmentioning
confidence: 99%